Avaliação do volume residual gástrico em indivíduos saudáveis usando a ultrassonografia, após ingestão de solução líquida enriquecida com carboidrato e glutamina : estudo clínico prospectivo, randomizado, duplo cego e cruzado - Gomes, Paulo Cesar (2013)
The abbreviation of preoperative fasting accelerates postoperative recover. The use of a solution enriched with maltodextrin 2 hours before the procedure is safe and recommended by the anesthesiology societies. The use of glutamine associated with maltodextrin would results in metabolic benefits, however this association can change the gastric residue and consequently the risk of aspiration. Objective: Evaluate the residual gastric volume by ultrasonografhy of 8 hours fasting and 120 and 180 minutes after ingestion of enriched solution with maltodextrin and maltodextrin and glutamine associated. Method: This was a randomized, prospective, double-blind and crossover clinical study. Were selected 20 healthy volunteers (n = 10 males and n = 10 female), initially submitted to the following sequence of evaluation, regardless the solution used: Tfasting with fasting of 8 hours (n = 20); intake of 12.5% maltodextrin solution and further evaluation, T120CHO (n = 20) and T180CHO (n = 20), which the volunteers were evaluated 120 and 180 minutes respectively. The same sequence was performed to 12.5% maltodextrin solution enriched with 15g of glutamine, in this case denominated T120GLN (n = 20) and T180GLN (n = 20). Results: There was no statistically significant difference between the Tfasting step compared to the T120CHO (13,56 ml vs. 16,32 ml, p>0,05) and T180CHO steps (13,56 ml vs. 14,60 ml, p>0,05) and so between Tfasting and T120GLN (13,56 ml vs. 15,63 ml, p>0,05) and T180GLN steps(13,56 mL vs 13,65ml, p>0,05). Conclusion: The results of this study show that the residual gastric volume returns to the value observed fasting for 8 hours after 120 and 180 minutes after ingestion of enriched solution with maltodextrin or maltodextrin associated with glutamine.